Fast Response Beam Coupling in Dye Doped Liquid Crystal Cells Sandwiched with ZnSe Coated Substrates. Issue 1748 (2nd July 2015) - Xue, Tingyu; Zhao, Hua; Meng, Cuiling; Fu, Jiayin; Zhang, Jingwen
ABSTRACT: In this paper we present fast response processes in dye doped liquid crystal cell with ZnSe layers on electrodes. Two-wave mixing and grating monitoring experiments were performed to characterize this liquid crystal system. With the help of photoconductive layers, the response time was reduced to a few milliseconds, which improved further the response rate in liquid crystal photorefractive system. A peak in response time versus applied voltage and unexpected oscillations in diffraction efficiency dynamics were observed, which implies unconventionally complex charge dynamics associated with SPPs excited at one of the photoconductive layer/liquid crystal interfaces.